Hope and Despair in Today’s World: Avery Dulles and Filipino Youth - Puen, Stephanie Ann Y (Archīum Ateneo, 2021)
Hope and activism form an important part of the Christian faith commitment; and as Avery Dulles’s work shows; such hope and activism entails a dynamic conversion in one’s faith commitment. Looking at Dulles’s work; I would like to draw out a message of hope that can speak to the situation today; bringing together Dulles’s method and work on faith; Church; and society. In response to the brief discussion above on hope and despair of the youth in response to today’s socioeconomic and political realities; I would like to emphasize three points from Dulles’s work: first; Dulles emphasizes that hope is rooted in the Christian faith commitment in Jesus Christ that entails conversion; second; that such a faith commitment supports and is supported by a vision of hope in the Kingdom of God; and third; that such a faith commitment is developed and strengthened within the context of community—that of the Church. I will end by applying this in particular to the Philippine setting; where hope and despair are particularly felt by the majority Catholic country amid grinding poverty; extrajudicial killings; and worsening living conditions.